The Influence of Health Education on Adolescents Knowledge of Reproductive Health in the Working Area of the UPTD Munjul Health Center (EKSAKTA: Berkala Ilmiah Bidang MIPA, 2023)
This study aims to identify adolescents' knowledge about reproductive health before and after health education is carried out in the working area of the UPTD Puskesmas Munjul Majalengka Regency in 2022. This type of research is a quantitative study with one group pre-test and post-test design. The population is 2467 people and the sample in this study is adolescents in the working area of the UPTD Munjul Health Center, Majalengka Regency, as many as 100 people in 2022. Data collection used a questionnaire. The data analysis technique used is the Wilcoxon test. The results showed that the average knowledge of adolescents about reproductive health before being given health education was 60.29% and after being given health education was 80.71%. The results of the hypothesis test with an alpha error rate of 0.05 obtained a value of p
Keywords: Adolescent; Health Education; Reproductive Health